Hubungan antara Tekanan Teman Sebaya dan Gaya Hidup dengan Perilaku Seksual Mahasiswa Laki-laki - Diana Evi Purwitasari Suswanto Putri; Istar Yuliadi; Rafika Nur Kusumawati (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
This study aims to determine the relationship between peer pressure and lifestyle with the sexual behaviour of male students. This study used cluster random sampling with 325 male undergraduate students from University X aged 18-22 years as respondents. The instruments used were the sexual behaviour scale (α=0.934), the peer pressure scale (α=0.940), and the lifestyle scale (α=0.955). The results showed that there was a significant relationship between peer pressure and lifestyle with sexual behaviour (Fcount=26,386 and p=0.000, p0.05) with a total effective contribution of 14.1%, there was a significant positive relationship between peer pressure and sexual behaviour (r = 0.257, p = 0.000) with an effective contribution of 6%, and there is a significant positive relationship between lifestyle and sexual behaviour (r = 0.295, p = 0.000) with an effective contribution of 8.1%.